Optimalisasi kinerja guru: menggali dampak kompetensi profesional, disiplin kerja, dan motivasi kerja pada Yayasan Pendidikan Siswarta Palangkaraya Kalimantan Tengah - Pitang, Antonius; Sunarto, Sunarto (Kuras Institute, 2024)
Purpose − The research’s aim is to know the influences of professional competences, discipline in work, and work motivation in partial either group on teacher performances of Siswakarya education foundation, Palangkaraya.. Method − This research is quantative research with ex-post facto’s research method. The research population is all teachers of Siswarta Palangkaraya Education Foundation with amount of 107 people. The sample is measured by the technic of cluster random sampling with sample people of 84. Data collecting using documentation and quisionere methods with Likert scala. Data is analyzed by descriptive analysis, corelation and regretion. Findings − The result of research shows that : Professional Competence, Discipline in Work, and Work Motivation absolutely influence on teacher performances of Siswarta Palangkaraya education foundation. In the meantime, Partial method does not influence on teacher performance. Discipline in Work and Work Motivation partially influence on teacher performance.